2016
DOI: 10.1038/pj.2016.43
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymerization of p-methylstyrene using various metal chlorides: design rationale of initiating systems for controlled polymerization of styrenes

Abstract: Cationic polymerization of p-methylstyrene (pMeSt) was examined using various metal chlorides as Lewis acid catalysts in dichloromethane. All of the catalysts used produced poly(pMeSt)s in the presence of 2,6-di-tert-butylpyridine (DTBP). However, the polymerization behavior differed depending on the type of metal chloride. The polymerization reactions conducted using SnCl 4 and ZnCl 2 proceeded in a controlled manner and yielded well-defined polymers, whereas metal trichlorides (for example, AlCl 3 , FeCl 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…However, it was somewhat similar to Olah's categorization of Lewis acids based on Friedel-Crafts reaction [61] . At 80 C, the trend also approximately agreed with those published by Saito, et al [68] for the metal chloride-catalyzed cationic polymerization of p-methylstyrene. As the metal part of the Lewis acid is often depicted as complexing with the substrate [69][70] , the following mechanism seems reasonable.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, it was somewhat similar to Olah's categorization of Lewis acids based on Friedel-Crafts reaction [61] . At 80 C, the trend also approximately agreed with those published by Saito, et al [68] for the metal chloride-catalyzed cationic polymerization of p-methylstyrene. As the metal part of the Lewis acid is often depicted as complexing with the substrate [69][70] , the following mechanism seems reasonable.…”
Section: Discussionsupporting
confidence: 90%
“…Kobayashi et al [62] proposed a kinetic and reactivity classification based on a large range of Lewis acids. Many other notable contributions to Lewis acid scales have also been made by several research groups over the years [63][64][65][66][67][68] . Table 4 and depicted in black (wheat starch sample), green (sample B3), blue (sample B2), and red (sample B1).…”
Section: Discussionmentioning
confidence: 98%
“…No shoulders in high‐ M w region were observed, indicating the absence of chain coupling reactions. However, the end‐chlorine groups did lose at above 90% monomer conversion, and no peaks around 5.9 ppm assigned to the structure resulting from the β ‐proton elimination 33,34 were observed in 1 H NMR spectra. Thus, the loss of living chain ends probably resulted from the intra‐molecular Friedel‐Crafts alkylation 42 .…”
Section: Resultsmentioning
confidence: 93%
“…During the cationic polymerization of styrene and its co‐polymerization with other monomers, it has been found that Friedel‐Crafts alkylation (intra‐ and inter‐molecular) of benzene rings of PS segments with reactive chain ends occurred 31‐34 . These side reactions are generally detrimental to the synthesis of polymers with linear structures in living cationic polymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Isotactic poly­( p -methylstyrene), hereinafter referred as iP p MS, although it has been studied for decades since early reports by Natta et al, has been considered as a noncrystalline polymer, and to date, no synthetic route has been established to produce a crystallizable fully isotactic P p MS; therefore, the properties and capabilities of this material have never been fully explored. In recent studies, some attempts to synthesize fully isotactic P p MS have been undertaken using cationic polymerization; however, isotactic pentad fractions of only around 40% were observed; therefore, the attributed properties to iP p MS, such as crystallinity, are questionable.…”
Section: Introductionmentioning
confidence: 99%